2020
DOI: 10.3390/microorganisms8060803
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Molecular Tools and In Vivo Models for the Study of Human Fungal Pathogenesis

Abstract: Pathogenic fungi represent an increasing infectious disease threat to humans, especially with an increasing challenge of antifungal drug resistance. Over the decades, numerous tools have been developed to expedite the study of pathogenicity, initiation of disease, drug resistance and host-pathogen interactions. In this review, we highlight advances that have been made in the use of molecular tools using CRISPR technologies, RNA interference and transposon targeted mutagenesis. We also discuss the use of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 240 publications
(265 reference statements)
0
11
0
Order By: Relevance
“…Agrobacterium tumefaciens mediated transformation systems for the BSI-relevant Malassezia species were developed, allowing direct gene manipulation to better understand gene function (Ianiri et al, 2016 ; Celis et al, 2017b ). With the recent improvements to the CRISPR/Cas9 strategy, this gene editing system has already contributed to various fungal virulence studies (Malavia et al, 2020 ), and also its first application for research in functional Malassezia genetics has recently been reported (Ianiri et al, 2019 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Agrobacterium tumefaciens mediated transformation systems for the BSI-relevant Malassezia species were developed, allowing direct gene manipulation to better understand gene function (Ianiri et al, 2016 ; Celis et al, 2017b ). With the recent improvements to the CRISPR/Cas9 strategy, this gene editing system has already contributed to various fungal virulence studies (Malavia et al, 2020 ), and also its first application for research in functional Malassezia genetics has recently been reported (Ianiri et al, 2019 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Different methods exist to genetically transform fungi, including protoplast-mediated, Agrobacterium-mediate, electroporation, and biolistic (23,24). These strategies require selectable markers, usually a drug-resistance gene or nutritional gene, to isolate cells that contain the desired construct.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, they became even a bigger problem due to the changes in today's modern lifestyle and socioeconomical activities, which accelerates the spread of infection much faster around the world [ 2 ]. Due to this, many advances in detection and treatment of infectious disease have been studied and reported in the past decades, including developing different types of vaccines, innovative technologies, e.g., single-cell based studies, CRISPR technologies, RNA interference that help us to explore infectious disease more [ [3] , [4] , [5] , [6] ]. Moreover, CAR- and TCR-T cell-based therapies have been also investigated as new candidates [ 7 ].…”
Section: Introductionmentioning
confidence: 99%